International trends in university governance autonomy, self-government and the distribution of authority - Shattock, Michael (Routledge, 2014)
"Governance is becoming increasingly important in universities just as it is in the wider world of commerce and banking. Historically, universities were run by their academic communities but as mass higher education has taken root, as university research has become a critical element in national economies and as the demand for more accountability both financial and in academic performance has grown, pressure has mounted for a 'modernisation' of governance structures"..
Includes bibliographical references and index
Keywords: EDUCATION / General; EDUCATION / Higher; POLITICAL SCIENCE / Public Policy / General; Universities and colleges -- Administration -- Cross-cultural studies; Education, Higher -- Administration -- Cross-cultural studies; Higher education and state -- Cross-cultural studies; Nationales Interesse; Hochschulorganisation; Internationaler Vergleich; Politische Steuerung; Hochschulpolitik; Aufsatzsammlung